ASEAN 2025: Toward Increased Investment in the Southeast Asia Region? - Ziegenhain, Patrick (President University, 2020)
One of the major targets of the ASEAN Economic Community is to achieve a higher influx of foreign direct investments (FDI) into the region. By analyzing recent economic developments and weighing opportunities and challenges, this paper argues that there are good chances for a higher level of FDI in ASEAN until 2025. There are, however, several hindrances including the resistance of the ASEAN member states to accept further economic integration and a missing common regulatory framework, which will make it difficult to receive significantly more FDI in the near future.